To include, to host and to share the bread: Pastoral care of families in irregular situations - Guerrero Rodríguez, S.J., Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The pastoral care of people in complex, difficult and irregular situations is a major concern in the Church. Pastoral action is needed assure our caring presence in the lives and in the life situations of the people, to accompany situations where people suffers: illness, family problems, etc. There is often a lack of preparation in the pastoral agents that led to ignore or to minimize the problem of domestic violence. Regarding divorce, it is necessary to continue in the reflection about how to articulate a pastoral for these situations considered irregulars by the Church. For many people these situations are a true rebirth after a long period of pain and loneliness. A pastoral action where the background and style are an offering of dialogue, host, and search for new horizons from an evangelical sense that look for the distant and try to update its message to today’s culture.